Endovascular treatment for traumatic scalp arteriovenous fistulas: results with Onyx embolization. (20th June 2013) - Dabus, Guilherme; Pizzolato, Raffaella; Lin, Eugene; Kreusch, Andreas; Linfante, Italo
Abstract : Background: Arteriovenous fistulas of the scalp (S-AVFs) are rare lesions and may occur spontaneously or secondary to trauma. The use of Onyx for the treatment of S-AVFs is not well established at this time. We discuss three cases of traumatic S-AVFs treated successfully with Onyx embolization alone or in association with coils. Methods: The database of patients treated at the Baptist Cardiac and Vascular Institute, Miami, Florida, was reviewed. All patients with traumatic S-AVFs treated with Onyx were included. Results: Two men and one woman with progressive enlarging pulsatile mass with bruit or tinnitus had angiographic evidence of S-AVF and were treated. In two patients the S-AVFs were secondary to hair transplantation. They were treated with Onyx-18 embolization as the single treatment modality. One patient with S-AVF resulting from temporomandibular joint arthroscopy was treated with coils and subsequent Onyx-34 embolization. In one patient, transarterial microcatheterization and injection of Onyx-18 was performed. In another patient, the intra-arterial approach was prevented by arterial vessel tortuosity. Therefore, access to the fistula was obtained through direct puncture of a large frontal vein; contrast injection confirmed the positioning of the needle within the draining vein of the AVF and Onyx-18 was then injected while the outflow vein was compressed. In the third patient in this series, coils were deployed to allow safer and more controlled injection of Onyx-34. No procedure related complications were noted. Post-embolization angiography demonstrated successful and complete occlusion of the AVF immediately after treatment. Follow-up revealed complete resolution of the symptoms. Conclusions: Our experience in this small series indicates that endovascular treatment of S-AVFs with Onyx is rapid, safe, and highly effective.